Echinochrome A inhibits epithelial–mesenchymal transition and induces cell death mediated by DNA damage in human triple-negative breast cancer cells - Soon Yong Park; Mi-So Jeong; Cong So Tran; Jinyoung Lee; Da-Young Eum; Seyeon Jung; Elena A. Vasileva; Seoung Rak Lee; Hyoung Kyu Kim; Natalia P. Mishchenko; Jin Han; Yoo Jin Choi; et al. (Journal of Functional Foods)
Echinochrome A (Ech A), a marine-derived compound from Scaphechinus mirabilis, is known for its potent antioxidant activity. Its pharmacological derivative, Histochrome, is used to treat ischemia and cardiovascular disorders. Triple-negative breast cancer (TNBC) is an aggressive subtype with poor prognosis and limited treatment options. This study explores the anticancer effects of Ech A on TNBC cells. Ech A showed dose-dependent cytotoxicity, resulting in 65–75 % cell death in BT549, SUM149, and SUM159 after 72 h of treatment at 50 μM, while no viability changes in MCF10A. At lower concentrations, Ech A suppressed TNBC cell migration and invasion by 60–80 %, along with downregulation of EMT markers Snail and Claudin-1. At higher doses, Ech A induced cell death via DNA damage. These results suggest that Ech A may serve as a promising therapeutic agent for TNBC by targeting metastatic potential and/or cell viability.